PERTUMBUHAN DAN LAJU EKSPLOITASI UDANG KELONG (Penaeus merguiensis) DI PERAIRAN KABUPATEN LANGKAT SUMATERA UTARA The Growth and Exploitation Rates of Kelong Shrimp (Penaeus merguiensis) in Langkat District, North Sumatera - Green Alfath Siregar; Yunasfi Djayus; Ani Suryanti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The samples of Kelong shrimps are 1758 which consist of 654 male shrimps and 1104 female shrimps. The growth pattern of Kelong Shrimps is negative allometric. The frequency distribution of the carapace length of Kelong Shrimps is in the range of 13.07-39.68 mm, the size group which is dominating the male Kelong Shrimps and female Kelong Shrimps is 24.57-25.88. The assumption of the Von Bertalanffy growth parameter of male Kelong Shrimps L∞ is 36.30 mm with K=0.5 per year, the assumption of the value of female Kelong shrimps L∞ is 41.91 mm with K=0.62 per year. The rates of the natural mortality (M) is 1.161 per year. The mortality caused by the arrest (F) is 1.365 per year show the exploitation rates is 0.54. The value E which is obtained, is showing the indication overfishing of Kelong Shrimps. The comparison of male and female Kelong shrimps is 1:1.688. The value of the condition factor which shows that Kelong Shrimps have the body shape which is flat (thin).Keywords: Growth, exploitation rates, Penaeus merguiensis, Langkat